Ladder Drill Terhadap Kemampuan Dribbling Pemain futsal Ekstrakurikuler SMPN 1 Ujanmas Kabupaten Muara Enim - Aldiyansyah Aldiyansyah; Widya Handayani; Sugarwanto Sugarwanto (CV. Ulil Albab Corp, 2026)
This study aims to determine the effect of ladder drill training on the dribbling ability of extracurricular futsal players at SMPN 1 Ujanmas, Muara Enim Regency. The research method used is an experimental method with a One Group Pre-test Post-test Design. The population in this study were all male students who participated in extracurricular futsal activities at SMPN 1 Ujanmas, Muara Enim Regency, totaling 20 people. The sampling technique used total sampling, so that the entire population was used as a research sample. The instrument used was a zig-zag dribbling test to measure students' dribbling ability. The treatment in the form of ladder drill training was given for 16 meetings with a frequency of 4 times a week. The data analysis technique used a normality test and a hypothesis test (paired sample t-test). The results showed that the average pre-test dribbling ability score was 15.19 seconds, while the average post-test score was 13.44 seconds. This indicates an increase in dribbling ability with an average difference of 1.75 seconds or 11.52%. The results of the hypothesis test obtained a significance value of 0.000 <0.05 and a calculated t value of 157.67> t table of 2.10, so that H₀ was rejected and H₁ was accepted. Thus, it can be concluded that ladder drill training has a significant effect on improving the dribbling ability of extracurricular futsal players at SMPN 1 Ujanmas, Muara Enim Regency.